MOTIVASI PELAYANAN PUBLIK SEBAGAI PREDIKTOR ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Arfah (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
The study examined the relationship between the Public Service Motivation and Organizational Citizenship Behavior. Location of research at the Department of Marine and Fisheries East Java Province. The population of the study was 75 employees and the sample used is 52 people. To test the pattern of model relationships established, the researchers used regresssion statistical method analysis. The results of this study prove that the Public Service Motivation has a significant and positive influence on Organizational Citizenship Behavior, as well as partially indicate that Commitment to Public Interest, Solidarity and Patriotism have a significant and positive impact on Organizational Citizenship Behavior, but Involvement in Public Policy Making has no significant effect to Organizational Citizenship.